An electrochemically neutralized energy-assisted low-cost acid-alkaline electrolyzer for energy-saving electrolysis hydrogen generation. Issue 12 (23rd January 2018) - Li, Yan; Chen, Junxiang; Cai, Pingwei; Wen, Zhenhai
Abstract : The ability to reduce the energy consumed and the cost in water splitting is crucial for the generation of hydrogen, which can be stored and then oxidized to deliver clean, abundant, and sustainable energy with the regeneration of water. Abstract : The ability to reduce the energy consumed and the cost in water splitting is crucial for the generation of hydrogen, which can be stored and then oxidized to deliver clean, abundant, and sustainable energy with the regeneration of water. Herein, we report an asymmetric electrolyzer with three-dimensional (3D) Ni2 P nanorod networks as bifunctional electrocatalysts for acidic cathode and alkaline anode that are separated by a bipolar membrane; this type of electrolyzer affords us with optimization in decreasing the energy required and maximizing the electrocatalysts: (1) pH gradient between an anolyte and a catholyte separated by a bipolar membrane provides the electrolyzer with additional electrochemical neutralization energy for facilitating water splitting and (2) efficiency of electrocatalysts can be maximized by offsetting the well-known mismatch of optimal conditions for electrocatalysts between the anode (normally alkaline) and the cathode (generally acidic). This unprecedented water electrolysis system can activate water splitting at an applied voltage of around 0.79 V that is significantly lower than the minimum theoretical voltage requirement (1.23 V), reducing electricity energy consumed by more than 35.8%.